2017
DOI: 10.1111/cea.12963
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of allergic asthma from 1996 to 2006 and further to 2016—results from three population surveys

Abstract: SummaryBackground: During the latter half of the 20th century, the prevalence of asthma and many other allergic diseases has increased. Information on asthma prevalence trends among adults after 2010, especially regarding studies separating allergic asthma from non-allergic asthma, is lacking.Objective: The aim was to estimate prevalence trends of current asthma among adults, both allergic and non-allergic, from 1996 to 2016. while the prevalence of non-allergic asthma remained stable around 3.4%-3.8%. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
165
6
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 47 publications
16
165
6
7
Order By: Relevance
“…In the latter study [25], asthma was associated with workers in trade and commerce as well as healthcare and administration, while in the current study we only found an association between healthcare and asthma. These differences could mirror the changes in working conditions between the late twentieth and early twenty-first centuries, but also changes in smoking habits and living conditions [28]. Our finding of an association between healthcare and asthma corresponds with a study from Finland published in 2001 [29] that showed associations between incident asthma and medical and nursing work.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the latter study [25], asthma was associated with workers in trade and commerce as well as healthcare and administration, while in the current study we only found an association between healthcare and asthma. These differences could mirror the changes in working conditions between the late twentieth and early twenty-first centuries, but also changes in smoking habits and living conditions [28]. Our finding of an association between healthcare and asthma corresponds with a study from Finland published in 2001 [29] that showed associations between incident asthma and medical and nursing work.…”
Section: Discussionsupporting
confidence: 84%
“…The strength with our study was the large population-based cohort with a high participation rate resulting in a representative study population. Furthermore, the questionnaire and questions [710,14,16,24,26,28,35] have been used in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of asthma increased during the 1900s and is now estimated at 8–10% among adults (Backman et al, ; Lötvall et al, ). The prevalence is higher among boys in childhood, but there is a shift in adolescence (Tollefsen et al, ), which also affects the prevalence among adults; where asthma is more common among women (Backman et al, ; Cydulka et al, ). Thus, it is one of the most common chronic diseases among pregnant women and may also increase the risk for preterm delivery (Mendola et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, the prevalence of these diseases is on the increase. While during the last decades this was typically observed in developed countries, numbers are also increasing in the developing world [2-5]. …”
Section: Introductionmentioning
confidence: 99%
“…In the USA, AR affects between 20 and 40 million people, of which approximately 20% are SAR, 40% PAR, and the remaining 40% reporting mix symptoms [5]. Backman et al [2] report that in Europe allergic asthma increased from 5% in 1996 to 6% in 2006 and further to 7.3% in 2016. The food allergy statistics are in similar ranges, with global prevalence being estimated as high as 10% in some countries [13].…”
Section: Introductionmentioning
confidence: 99%